Pembangunan Agrowisata di Desa Trimulyo, Kecamatan Jetis, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta - Pratama, Yohanes Mario (Jurnal Atma Inovasia, 2022)
Trimulyo Village, Jetis District, Bantul Regency, Yogyakarta Special Region Province has one of the most abundant agricultural products, namely peanuts. However, there are still not many farmers who realize the high potential of peanuts as an agricultural commodity and have not maximized land management both from the planting method and the yield of peanuts. This community service program aims to increase the economic value of peanuts through the manufacture of peanut butter and peanut agro-tourism sites. The data collection method used in this study used a secondary data collection method that was arranged systematically so that it could be easily understood. The program is carried out by providing design designs for facilities in agro-tourism in the form of gates, parking areas, gift centers, multi-purpose rooms, gazebos, and agro-tourism areas. In addition, it is explained related to the process of making peanut butter and packaging so that it can be a souvenir from Trimulyo Village. This program certainly requires support from various parties such as the government and village communities. With this program, it is hoped that it can attract the attention of tourists in the future so that it can help the economy of the Trimulyo Village community.